Determinant of Entrepreneurship Action of Resettled Peasant Displaced By Land Acquisition - Sari, Embun; Winoto, Joyo; Soetarto, Endriatmo; Asikin, Zenal (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: In Indonesia, land acquisition policies prioritize providing compensation in the form of cash. This policy allows the community to obtain replacement land, investment, business capital, etc. Entrepreneurship is widely recommended as a more sustainable solution for the livelihoods of peasants who have lost their agricultural land. Entrepreneurship is a strategic solution for unemployment and employment discrimination of land-lost peasants. Purpose: This research examines the entrepreneurial actions of peasants who lost land due to land acquisition in Indonesia. Design/methodology/approach: The entrepreneurial actions of peasants who lost land due to land acquisition were revealed using questionnaire survey data from 125 farming households relocated due to the construction of an international airport in Kulon Progo, Yogyakarta. Finding/Result: The research results show that entrepreneurial actions after land acquisition are significant with the variables of intention (feasibility), age, income, and understanding of land acquisition policies. Displaced peasants who have the confidence to conduct entrepreneurship are primarily in their older age with higher incomes and better acceptance of land acquisition policy.Conclusion: Job/business training must continue on an ongoing basis, and mentoring and supervision must be carried out until people feel capable of becoming independent entrepreneurs. Originality/value (State of the art): This research was the first study on land-lost peasants’ entrepreneurship due to land acquisition in Indonesia. The research results were expected to provide new evidence and understanding regarding the influence of land-lost farmers' knowledge of land acquisition policies on entrepreneurial actions. Keywords: cash compensation, entrepreneurship action, displacement, land acquisition, resettled peasant